The Excellence of Performance, Semen Quality and Testosterone Levels on Bull in Teaching Farm, Faculty of Veterinary Medicine, Universitas Airlangga - Srianto, Pudji; Sardjito, Trilas; Utomo, Budi; Widodo, Oky Setyo (Jurnal Medik Veteriner, 2021)
Study on performance, semen quality and testosterone levels of 2 young bulls (age range 3-5 years) Limousine and Simental and 2 old bulls (age range 6-8 years) types Limousin and Simental have been carried out in the Teaching Farm, Faculty of Veterinary Medicine, Universitas Airlangga. This study aimed to determine the performance, semen quality and testosterone levels can be used as a guideline whether or not the ejaculate of young and old bulls should be continued into frozen semen. Performance tests were carried out using measuring sticks and weight bands, semen quality tests included macroscopic and microscopic tests, semen concentration using a spectrophotometer and testosterone test using the Sandwich-ELISA method. The mean results of the performance test in young bulls were, while the mean for older bulls were: body weight 700 kg; hump height 136.5 cm; circumferens of chest 213 cm; body length 171 cm and scrotal circumference 35.5 cm. The performance test for old bulls is body weight 840 kg; hump height 143 cm; circumferens of chest 225.5 cm; body length 177.5 cm and scrotal circumference 40.25 cm. Mean macroscopic of semen examination for young bulls, mean volume 8 cc; milky white color; characteristic odor; The degree of acidity was 6.5 and mucous consistency, while for the old bulls the volume was 6.85; milky white color; characteristic odor; 6.5 degrees of acidity and mucous consistency. The mean microscopic examination for young bulls was mass movement ++ / +++; individual movement 80/3; concentration 745.5 million / ml; abnormalities 3% and 92.25% viability, for old bulls: movement mass ++ / +++; individual movement 77.5 / 3; concentration 1291.5 millon / ml; abnormalities 5% and viability 90%. Examination of serum testosterone levels using the Sandwich-ELISA technique was obtained by an average of 1.299 ± 0.1598 ng/ml in young bulls and 1.101 ± 0.1502 ng/ml in older bulls. This study concluded that young bulls and old bulls in the Teaching Farm, Faculty of Veterinary Medicine, Universitas Airlangga in terms of performance, semen quality and testosterone levels are suitable for processing into high quality frozen semen.